COVID-19 and the Mental Health of People From Refugee Backgrounds. (October 2020) - Rees, Susan; Fisher, Jane
Approximately 1 in 10 of the current 26 million people who are refugees reside in high-income countries. They have commonly experienced trauma related to violence, insecurity, persecution and shortage of food and medicine. Our research suggests that COVID-19 and its health and social sequalae may be triggering past traumatic reactions, exacerbating mental health problems and undermining functioning. The purpose of this article is to promptly communicate these anecdotal findings to general health practitioners to ensure informed and sensitive health care delivery to this vulnerable population.